2022
DOI: 10.3389/fmicb.2022.730075
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effects of Pore Water Velocity and Soil Heterogeneity on Bacterial Transport: Intact vs. Repacked Soils

Abstract: Graphical AbstractDepth profile of pore water velocity effect in differently structured soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This observation aligns with previous research on the influence of ionic strength and pore water velocity on attachment/detachment dynamics (J. Chen et al, 2022;Knappett et al, 2008). Compared to the traditional method, the values of both 𝑘 a and 𝑘 d obtained through the RP method were marginally lower.…”
Section: Comparison Of Traditional Methods and Rp Methodssupporting
confidence: 91%
“…This observation aligns with previous research on the influence of ionic strength and pore water velocity on attachment/detachment dynamics (J. Chen et al, 2022;Knappett et al, 2008). Compared to the traditional method, the values of both 𝑘 a and 𝑘 d obtained through the RP method were marginally lower.…”
Section: Comparison Of Traditional Methods and Rp Methodssupporting
confidence: 91%
“…Packing and/or differences in grain size may have also contributed to increasing pore-scale complexity which has been observed to widen pore-water velocity distributions − and could lead to more colloids reaching the grain surface based on previous pore-scale simulation studies. ,− Under unfavorable attachment conditions, bacteria attachment is largely driven by local variations in velocity. This has been observed in experiments and models at grain–grain contacts, near grain surfaces where roughness leads to enhanced attachment, , and regions of decreasing pore water velocity. ,,− …”
Section: Resultsmentioning
confidence: 58%
“…Pore water velocity showed highest importance in the predictions of k and λ . This is because bacterial transport could be increased by increasing pore water velocity ( Bradford et al, 2006 ; Choi et al, 2007 ; Chen et al, 2022 ). Higher pore water velocity is accompanied by higher water shear force and less bacteria-soil contact time, which can reduce bacterial mechanical filtration and bacterial attachment, respectively ( Hendry et al, 1999 ; Li et al, 2005 ; Syngouna and Chrysikopoulos, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…For porous medium type, bacterial concentration, organic content, and saturated hydraulic conductivity, the SHAP contribution shows relatively aggregated distribution. Many studies showed that the intact soil could greatly facility bacterial transport because of preferential flow in macropore-dominated pathways ( McLeod et al, 1998 ; Safadoust et al, 2011 ; Chen et al, 2022 ). Nevertheless, the effect of intact soil or disturbed soil was not obvious in our predictive models.…”
Section: Resultsmentioning
confidence: 99%